1988
DOI: 10.1002/1097-0142(19880901)62:5<905::aid-cncr2820620509>3.0.co;2-3
|View full text |Cite
|
Sign up to set email alerts
|

Successful imaging of human cancer with indium-111-labeled phospholipid vesicles

Abstract: Twenty-four patients with proven primary and/or metastatic cancer received single intravenous injections of phospholipid vesicles containing 0.5 mCi of Indium-111. Gamma camera scintigraphy 1 to 72 hours later visualized tumors in 22 patients (92%), including carcinomas of breast, lung, colon, prostate, kidney, cervix, thyroid, and soft tissue sarcoma, lymphoma, and melanoma. Tumor sites that were identified included soft tissues, bone, lung, liver, lymph node, and spinal cord. There were only two false-positi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
35
0

Year Published

1991
1991
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(37 citation statements)
references
References 19 publications
2
35
0
Order By: Relevance
“…Successful therapy requires the site-specific delivery of relatively large amounts (15)(16)(17)(18)(19)(20) jig of B per g of tissue) of boron to tumors (2). Strategies employed have included the use of boron compounds with some natural affinity for tumors, such as 4-(dihydroxyboryl)phenylalanine (BPA) (3) or the mercaptoundecahydro-closo-dodecaborate dianion (B12H,,SH2-; BSH) (4); the attachment ofboron-containing species to other molecules such as porphyrins (5); and the conjugation of boron-rich compounds with tumor-specific monoclonal antibodies and their fragments (6).…”
supporting
confidence: 85%
See 1 more Smart Citation
“…Successful therapy requires the site-specific delivery of relatively large amounts (15)(16)(17)(18)(19)(20) jig of B per g of tissue) of boron to tumors (2). Strategies employed have included the use of boron compounds with some natural affinity for tumors, such as 4-(dihydroxyboryl)phenylalanine (BPA) (3) or the mercaptoundecahydro-closo-dodecaborate dianion (B12H,,SH2-; BSH) (4); the attachment ofboron-containing species to other molecules such as porphyrins (5); and the conjugation of boron-rich compounds with tumor-specific monoclonal antibodies and their fragments (6).…”
supporting
confidence: 85%
“…Previous research, utilizing pure synthetic phospholipids, has produced useful unilamellar vesicles that have been shown to deliver their contents preferentially to tumor cells in animals (11,14) and humans (15,16) such that the tumor levels of effector molecules are 5-10 times that of normal tissue, including blood.…”
mentioning
confidence: 99%
“…Animal studies have shown that liposomes can decrease the toxicity of several antitumnor and antifungal drugs, leading to several recent clinical trials with promising results (2)(3)(4)(5)(6). In addition, liposomes have been shown to be efficient carriers of antiparasitic drugs for treating intracellular infections of the reticuloendothelial system (RES), in activating macrophage cells to become tumoricidal in models of metastasis, and in enhancing the immune response to encapsulated antigens, thus facilitating the formulation of artificial vaccines (7,8).…”
supporting
confidence: 73%
“…[15][16][17][18] The tumor accumulation levels of [Cu-64]-liposomes in the included carcinomas that displayed EPR effects (based on increasing accumulation between scans) are compatible to those reported in previous human cancers evaluated by gamma camera and SPECT imaging. 15 The authors report tumor uptake from tumor size estimations to range from 2.7 -53.0 %ID/kg.…”
Section: Discussionmentioning
confidence: 99%
“…Current knowledge on the EPR-effect in human tumors is based on studies of low-resolution single photon imaging techniques of radiolabeled liposomes. [15][16][17][18] Liposome uptake has been investigated in a Kaposi sarcoma and a lymphoma patient. 16 Furthermore, targeting and delineation has been investigated in eight high-grade gliomas 17 and positive tumor identification using radiolabeled phospholipid vesicles in 22 of 24 patients suffering from a few malignancies.…”
Section: Abstract Nanomedicine Cancer Epr-effect Drug Delivery Imentioning
confidence: 99%